Caracterização das comunidades de peixes de duas lagoas marginais na bacia do Alto Paranapanema - Turco, Debora Pardini Lo (2018)
Marginal lagoons are considered an integral part of lotic systems, interacting with rivers through the exchange of water, nutrients and living organisms. They play an important role in the maintenance of biodiversity, especially the ichthyofauna, serving as a refuge for predators, nursery and feeding grounds. This work had as objective the characterization of the ichthyofauna of two marginal lagoons of a preserved section of the Paranapanema river, in order to validate the importance of these environments for the preservation of species of fish and their function as nursery and to record the basal frequency of micronuclei and nuclear morphological abnormalities in erythrocytes of the captured fish, comparing these frequencies with the control groups of other works of the literature. In general, the ichthyofauna sampled was composed mainly of small species, with low migratory capacity and life cycle associated to the marginal lagoons, depending on them for feeding / growth or reproduction. The disparities found in the communities of these lagoons in the different campaigns may reflect the degree of connectivity of these environments to the river; since the similarity between the lagoons was greater in the second campaign, which coincided with the beginning of the rainy season. The micronucleus frequencies and nuclear anomalies showed values similar to those observed in the literature for the negative control groups of the different species analyzed, evidencing that these lagoons can be considered little impacted by pollutants.